2022
DOI: 10.1002/ase.2160
|View full text |Cite
|
Sign up to set email alerts
|

Universal design for learning in anatomy education of healthcare students: A scoping review

Abstract: In recent years, the hours dedicated to teaching anatomy through dissection and didactic lectures to students of medicine and allied health professions, in the physical university environment, has reduced due to the advancement of technology and competition with teaching time from other disciplines (Papa & Vaccarezza, 2013;Wong et al., 2020). Additionally, there are concerns among medical and dental practitioners about poor anatomical knowledge among recent healthcare graduates (Durham et al., 2009;Fillmore et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…This suggests that educators are already incorporating elements of the UDL framework, albeit potentially unknown to themselves. A scoping review analyzing the design and delivery of anatomy curricula in healthcare programs in higher level institutions revealed that when designing curricula, educators may incorporate methods which align with the UDL framework, without explicitly stating that UDL was utilized (Dempsey et al, 2022 ). However, there are still a number of checkpoints which very few respondents of this study identified in their curriculum design.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that educators are already incorporating elements of the UDL framework, albeit potentially unknown to themselves. A scoping review analyzing the design and delivery of anatomy curricula in healthcare programs in higher level institutions revealed that when designing curricula, educators may incorporate methods which align with the UDL framework, without explicitly stating that UDL was utilized (Dempsey et al, 2022 ). However, there are still a number of checkpoints which very few respondents of this study identified in their curriculum design.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these teaching modalities have been identified as critical for students' anatomy learning experience (Farkas et al, 2016 ). Recent literature indicates that these traditional methods should not be used in isolation but rather alongside new innovative methods to enhance accessibility of learning material and to promote student engagement and interest in anatomy (Dempsey et al, 2022 ; Iwanaga, Loukas, et al, 2021 ; Lochner et al, 2016 ). For example, studies have identified that modern teaching strategies, such as gamification, virtual and augmented reality which align with multiple means of representation, result in similar levels of knowledge acquisition and collaborative activity as traditional methods (Moro et al, 2021 ; Rezende et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations